Effects of dopaminergic replacement therapy on motor speech disorders in Parkinson's disease: longitudinal follow-up study on previously untreated patients - Rusz, Jan; Tykalová, Tereza; Klempíř, Jiří; Čmejla, Roman; Růžička, Evžen (Journal of neural transmission (Vienna, Austria, 2016)
Although speech disorders represent an early and common manifestation of Parkinson's disease (PD), little is known about their progression and relationship to dopaminergic replacement therapy. The aim of the current study was to examine longitudinal motor speech changes after the initiation of pharmacotherapy in PD. Fifteen newly-diagnosed, untreated PD patients and ten healthy controls of comparable age were investigated. PD patients were tested before the introduction of antiparkinsonian therapy and then twice within the following 6 years. Quantitative acoustic analyses of seven key speech dimensions of hypokinetic dysarthria were performed. At baseline, PD patients showed significantly altered speech including imprecise consonants, monopitch, inappropriate silences, decreased quality of voice, slow alternating motion rates, imprecise vowels and monoloudness. At follow-up assessment, preservation or slight improvement of speech performance was objectively observed in two-thirds of PD patients within the first 3-6 years of dopaminergic treatment, primarily associated with the improvement of stop consonant articulation. The extent of speech improvement correlated with L-dopa equivalent dose (r = 0.66, p = 0.008) as well as with reduction in principal motor manifestations based on the Unified Parkinson's Disease Rating Scale (r = -0.61, p = 0.02), particularly reflecting treatment-related changes in bradykinesia but not in rigidity, tremor, or axial motor manifestations. While speech disorders are frequently present in drug-naive PD patients, they tend to improve or remain relatively stable after the initiation of dopaminergic treatment and appear to be related to the dopaminergic responsiveness of bradykinesia.
Keywords: antiparkinsonika; Levodopa; Speech Disorders; Male; longitudinální studie; levodopa; následné studie; Hypokinetic dysarthria; Parkinson’s disease; Adult; Aged; dospělí; mužské pohlaví; senioři; Follow-Up Studies; Speech impairment progression; lidé; ženské pohlaví; Humans; poruchy řeči; Longitudinal Studies; Antiparkinson Agents; Female; Parkinson Disease; Parkinsonova nemoc; Acoustic analysis; lidé středního věku; Middle Aged